Reclamation condition of saline soils and scientific bases of its improvement. - Amrulloyeva Shoira Komilovna (Genius Publishing Group, 2022)
This article provides information on the reclamation of saline soils and the scientific basis for its improvement, reclamation of saline and saline soils.
Keywords: Salinity; saline soils; soil; gypsum